Agriculture's prominence in the INDCs - Richards, Meryl B.; Gregersen L; Kuntze, V.; Madsen S; Oldvig MB; Campbell, Bruce M.; Vasileiou, Ioannis (2015)
Analysis of agriculture in countries’ climate change mitigation and adaptation strategies finds: Most Parties to the UNFCCC include agriculture in their mitigation targets (80%) and adaptation strategies (64%); Non-annex 1 Parties note the need for international financial support to implement their INDCs and raise the ambition of their contributions; For countries to meet their targets, climate finance will need to address agriculture.